Hubungan antara Kesadaran Metakognitif dan Prestasi Akademik Mahasiswa Pendidikan Agama Islam - Alma'as, Lutfi Aribha; Khasanah, Uswatun; Romlah, Listiyani Siti; Kuswanto, Anggil Viyantini; Hijriyah, Umi (Ta’allum: Jurnal Pendidikan Islam, 2024)
Research related to the relationship between metacognitive awareness and academic achievement aims to examine the relationship and understand more about the role of metacognitive awareness in achieving optimal academic achievement for Islamic Religious Education students. This research uses a quantitative approach and type of correlation research. The data collection technique used the distribution of the Metacognitive Awareness Inventory (MAI) questionnaire adapted from Schraw and Dennison (1994). The research sample consisted of 96 students selected by simple random sampling technique. Data analysis used a correlation test to see whether or not there was a relationship between metacognitive awareness and academic achievement. The test was strengthened by simple linear regression test. The results showed that a correlation of 0.663 was found, which showed that the two variables had a strong correlation. And a significance value of .000 was found, which if the sig. < .01 means there is a significant relationship between the two variables. In the simple linear regression test, it produces a value of F hitung = 73.610 with a significance level of 0.000, which if the sig.<0.05 means that there is a significant influence between metacognitive awareness and the GPA of Islamic Religious Education students.